Sustainable Crop Production Systems and Human Nutrition - Roberts, Daniel P.; Mattoo, Autar K. (Frontiers in Sustainable Food Systems, 2019)
There is a pressing need for redesigning agriculture to achieve sustainability and for utilizing modern genetic tools, including genetic engineering, to add nutritional value to crops for the benefit of the diverse human population. Collectively, plant foods contain most minerals, macronutrients (calories), and micronutrients essential for human nutrition. These plant foods also contain a range of bioactive compounds that can play important roles in the prevention of chronic diseases including heart disease, cancer, stroke, diabetes, Alzheimer's, cataracts, and age-related functional decline. However, these bioactive nutrients are often present at marginal concentrations in edible plant tissues in regard to human nutrition/prevention of disease. The quantity of these nutrients in edible plant tissues is primarily dependent on crop genetics and regulated by complex and overlapping mechanisms in response to developmental and environmental cues. Environmental cues are naturally occurring—temperature, light intensity, and other stressors, or result from crop production system components—fertilizer, tillage operations, etc. One strategy for sustainable, next-generation crop development is to design cropping systems that have minimal or lesser impact on the environment and to use genetic approaches to enhance crop nutritional content. This strategy is appealing since crop genetics is the primary driver of plant nutrient content and because purely managing crop production fields to optimize crop nutrient content is extremely challenging if not impossible. As an example we present the development of a next-generation sustainable tomato production system with beneficial impacts on tomato physiology and nutritional quality of the tomato fruit. Our analysis of the metabolomes of tomato cultivars in this and other cropping systems highlights the need for robust cultivars that consistently express nutritional and other desirable traits across cropping systems and under differing environmental conditions.